STRATEGI ADAPTASI CULTURE SHOCK MAHASISWA PERANTAU PADA MAHASISWA AFIRMASI ASAL PAPUA DI UNIVERSITAS RIAU - Simanullang, Farida Ayuningsi; ', Resdati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Culture shock phenomenon was felt by Affirmation students from Papua at the University of Riau, in this case they experienced feelings of anxiety and fear of starting socialization with friends or the community due to cultural differences between Papua and Pekanbaru. The purpose of this research is to find out the culture shock factors that occur in Affirmation students from Papua and to find out the adaptation strategies carried out by Affirmation students from Papua in dealing with culture shock. The method used in this research is descriptive qualitative, with the number of subjects being 6 Affirmation students from Papua at the University of Riau who were selected using a purposive sampling technique. Data collection uses in-depth interview techniques and documentation. The theory used in this study is the theory of Kalvero Oberg, namely culture shock, which is caused by anxiety caused by the loss of symbols in a social interaction. The results of this study indicate that there are several factors of culture shock experienced by Affirmation students from Papua (ADIK), namely social factors, geographical factors (weather), everyday language factors, technological factors, economic factors, religious factors and food factors. From this form, some of the subjects did not have too many problems with the factors that caused the culture shock, they were still able to adjust well over time. From the obstacles they experience, there are several strategies or solutions that are carried out to overcome them, namely the first by way of cooperation (comformity) such as building friendships, joining organizations in higher education, participating in religious activities, and the second by means of innovation such as trying to open oneself to the social environment. Keywords: Afirmation, Culture Shock, Strategy, Students